Deciphering the evolution of digital therapeutics: A bibliometric analysis of clinical trials - Kavita R. Garg; Vinaytosh Mishra; Krishan K. Pandey; Gaurav Kabra; Ashish Kaushal (Proceedings of Singapore Healthcare)
Background Fewer studies have analyzed the clinical trials within the digital therapeutics (DTx) domain, lacking the comprehensive scope to capture the full spectrum of global DTx research. This study provides a comprehensive bibliometric and text-mining analysis of the global research landscape of DTx clinical trials. Objectives This study aims to analyze the global research landscape of DTx clinical trials across diverse indications using bibliometric and text-mining analysis. Methods We utilized a data-driven approach to analyze 99 articles retrieved from databases (PubMed, Scopus, and Web of Science) spanning nearly a decade (2014-2023), allowing for a more thorough understanding of the progression and trends in DTx research. R Studio package and Vosviewer were used for data analysis. Results The findings showed a 56.5% annual growth in scientific production since 2020, with the most cited country, contributing author, and local cited source being the United States, Gerwien R, and Journal of Medical Internet Research, respectively. Trending research topics include sleep disorders, diabetes, anxiety, depression, mental health, blood pressure monitoring, and hypertension. Conclusions The findings emphasize the need for more robust randomized controlled trials to evaluate the effectiveness of DTx interventions and offer new insights and directions for future research in this rapidly growing field. This contribution is particularly significant given the increasing reliance on digital technologies for managing various medical conditions and improving patient-reported and healthcare outcomes.